HUBUNGAN PELAYANAN PRIMA DENGAN KEPUASAN PELANGGAN PT KERETA API INDONESIA (PERSERO) PADA STASIUN PASAR SENEN (STUDI KASUS: KA PROGO PASAR SENEN-LEMPUYANGAN KELAS EKONOMI) - Suhartono Suhartono; Eka Putri Nur Azizah; Lukman Hakim; Hartanti Hartanti (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
PT Kereta Api Indonesia (Persero) is a land transportation service company that prioritizes customer satisfaction. The purpose of this study was to determine excellent service, to determine customer satisfaction and to determine the relationship of excellent service with customer satisfaction at Pasar Senen Station in Jakarta. The research method uses quantitative methods with questionnaires and interviews analyzed using SPSS 22.0. Population of 100 respondents using saturated sample techniques. The results showed that the correlation of 0.746 which means that there is a very strong relationship between excellent service and customer satisfaction. In the coefficient of determination test it is known that the R Square value of 55.6% and the remaining 44.4% is influenced by other factors.Keywords: Excellent Service, Customer Satisfaction